(E)-1-(Benzo[d][1,3]dioxol-5-yl)-5,6,6-trimethylhept-4-en-3-one - Mario Rico-Molina; Joaquín Altarejos; Sofía Salido (Molbank)
The title compound (1) was obtained within a project to synthesize analogs of the antiepileptic drug stiripentol. Compound 1 was synthesized by aldol addition of the lithium enolate of 4-(benzo[d][1,3]dioxol-5-yl)butan-2-one (2) to 3,3-dimethylbutan-2-one (3), followed by the dehydration of the resulting β-hydroxy-ketone under acid processing. The structure of 1 was established by 1D and 2D NMR spectroscopy and high-resolution mass spectrometry.